2018
DOI: 10.1155/2018/4864107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Oxytocin Signaling at the Synaptic Connection

Abstract: Aberrant regulation of oxytocin signaling is associated with the etiology of neurodevelopmental disorders. Synaptic dysfunctions in neurodevelopmental disorders are becoming increasingly known, and their pathogenic mechanisms could be a target of potential therapeutic intervention. Therefore, it is important to pay attention to the role of oxytocin and its receptor in synapse structure, function, and neuron connectivity. An early alteration in oxytocin signaling may disturb neuronal maturation and may have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 88 publications
1
68
0
1
Order By: Relevance
“…Reduced dendritic spine densities in OTR KO mice. Previous studies suggest that OT signaling in developing brains plays critical roles in development and function of mature synapses 12,13 . Here, we used Golgi staining to label and compare synaptic densities of Otr KO (Otr Venus/Venus ) and heterozygote (Otr Venus/+ ) littermate mice at P21 (N = 3 mice per genotype).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced dendritic spine densities in OTR KO mice. Previous studies suggest that OT signaling in developing brains plays critical roles in development and function of mature synapses 12,13 . Here, we used Golgi staining to label and compare synaptic densities of Otr KO (Otr Venus/Venus ) and heterozygote (Otr Venus/+ ) littermate mice at P21 (N = 3 mice per genotype).…”
Section: Resultsmentioning
confidence: 99%
“…This transient OTR expression in the developing cortex is thought to play an important role in facilitating neural circuit maturation 8,9 . For instance, OTR in postnatally developing brains has been implicated in multisensory binding 10 , maturation of GABAergic neurons 11 , and synapse formation and maturation between neurons 12,13 .…”
mentioning
confidence: 99%
“…Oxytocin signaling pathway has been known to regulate synapse structure, function and neuron connectivity during social interaction 54,55 . Recent studies have found that oxytocin signaling is involved in the differentiation of neuronal progenitor cells 56 , synapse formation 57 and the formation of neural circuits during brain development 58,59 . MAPK signaling pathway 60,61 , estrogen signaling pathway 62,63 and cAMP signaling pathway 64,65 are important for synaptogenesis and synapse pruning and refining.…”
Section: Resultsmentioning
confidence: 99%
“…Oxytocin receptor signaling activates MEF2 in a context-dependent manner and thereby induces morphological changes, e.g., neurite retraction (50). Morphological changes in turn determine the synaptic strength and therefore connectivity between oxytocin receptor positive neurons (76). Oxytocin-sensitive neurons are located in brain regions that are part of the salience network (80), which has been shown to be responsive to oxytocin (42) and modulates anxiety-like behavior or the stress response (86, 87).…”
Section: Mef2-driven Mechanisms Affecting Neuronal Connectivitymentioning
confidence: 99%